Coffee Tourism Development Potential in Banyuwangi Regency, East Java - Basalamah, Anwar; Abdillah, Fitri; Susanto, Shandy; Permata, Stella; Windawaty, Herry (Sadar Wisata: Jurnal Pariwisata, 2023)
Cultural diversity and local wisdom become a promising attraction in advancing Indonesian tourism. Coffee Tourism is one of the tourist attractions that can offer a unique travel experience. The aim of this research is to know the potential and strategy of development of Coffee Tourism in Banyuwangi district, East Java. Using qualitative research methods, data processing is carried out through observations, interviews and documentation related to the potential and development strategies of Coffee Tourism in the region. Sample on this study was more focused on stakeholders related to coffee tourism, such as local governments, local tourism agencies, coffee farmers, coffee entrepreneurs, coffee-based micro business, and tourists. This study focuses on four dimensions of tourist attraction components: attractions, accessibility, amenities, and ancillary services. The study's findings indicate that Banyuwangi Regency's tourism attraction component has sufficient potential as a coffee tourism. The four tourist attraction components in the Banyuwangi district have generally met the requirements for the development of coffee tourism, despite some remaining flaws. Because of Banyuwangi's distinct cultural advantages, coffee tourism in this region can be intriguing and promising